2021
DOI: 10.2147/jmdh.s309517
|View full text |Cite
|
Sign up to set email alerts
|

Community Psychiatry Care: An Urgent Need in Nigeria

Abstract: Nigeria's mental health policy was formulated in 1991, but it did not make adequate provision for community-based psychiatric care. Since there are only seven government-owned psychiatry facilities in Nigeria and these are always overwhelmed, there is the need to overhaul the existing policy and emphasise the urgency of a shift from inpatient psychiatric mental healthcare towards a community-based multidisciplinary psychiatric healthcare system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…Poor and underserved populations are particularly vulnerable to the adverse effects of mental disorders, experiencing a more severe impact on functioning, having drastically limited access to early intervention, and discontinuing treatment due to cost [ 11 ]. Significant factors limiting access to formal mental health care in Nigeria include the scarcity of mental health specialists, with only 0.15 psychiatrists per 100 000 of the population (compared to the US’s 10.54 per 100 000) [ 12 ], a lack of community-level care for mental disorders [ 13 ], the limited integration of mental health integration in primary care [ 14 ], and the pervasive stigma towards mental disorders, even among health care providers [ 15 , 16 ]. In Nigeria, stigma has been widely documented as a deterrent to help-seeking [ 17 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Poor and underserved populations are particularly vulnerable to the adverse effects of mental disorders, experiencing a more severe impact on functioning, having drastically limited access to early intervention, and discontinuing treatment due to cost [ 11 ]. Significant factors limiting access to formal mental health care in Nigeria include the scarcity of mental health specialists, with only 0.15 psychiatrists per 100 000 of the population (compared to the US’s 10.54 per 100 000) [ 12 ], a lack of community-level care for mental disorders [ 13 ], the limited integration of mental health integration in primary care [ 14 ], and the pervasive stigma towards mental disorders, even among health care providers [ 15 , 16 ]. In Nigeria, stigma has been widely documented as a deterrent to help-seeking [ 17 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported an inverse correlation between eHealth literacy and depression and that improving eHealth literacy may contribute to maintaining good psychological well-being ( 21 , 22 ). Mental health services are severely sparse in Nigeria, and related stigma persists ( 42 ). Hence, it is likely that individuals are accessing online sources of mental well-being information, and this could be harnessed to help manage their anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…The high rate of mental disorders across developed and developing countries has been made worse by the psychological challenges associated with the emergence of Stanley et al COVID-19 (Moynihan et al, 2021). Approximately 71% of people diagnosed with mental disorders lack access to any treatment; only 0.6% of these who live in developing countries have access to treatment from mental health professionals (Uwakwe, 2019; Soroye et al, 2021). This review shows that this shortage is likely to worsen for specialties like psychiatry, highlighting the need for policies and deliberate actions by training institutions to provide career guidance for health science students, to address the global need across specialties.…”
Section: Factors Influencing Career Choices Among Health Science Stud...mentioning
confidence: 99%